VOICE DISORDERS IN TRANSGENDER PERSONS: ETIOLOGY, CLINICAL PICTURE AND THERAPEUTIC APPROACHES - Ilic Savic, Ivana; Petrović-Lazić, Mirjana (HEALTH CARE, 2025)
Voice disorders in transgender people represent a significant challenge in the process of gender affirmation, because the voice directly affects the perception of gender identity and psychosocial well-being. The aim of this paper is to provide a comprehensive overview of the etiology, clinical picture and therapeutic approaches of voice disorders in transgender people. Hormonal, anatomical and psychosocial factors influencing voice changes, typical symptoms and acoustic characteristics, as well as various treatment methods, including vocal therapy, phonosurgery and a multidisciplinary approach, were analyzed. Hormone therapy in trans men leads to significant voice changes, while in trans women it is often not enough to achieve the desired gender perception, and additional vocal therapy or phonosurgery is needed. Vocal therapy, when necessary, phonosurgery are effective methods for voice correction, and a multidisciplinary approach enables optimal outcomes and improvement of quality of life. However, the lack of standardized protocols and longitudinal studies highlights the need for further research and individualization of therapy. In conclusion, successful intervention in voice disorders in transgender persons requires the integration of medical, speech therapy and psychological methods, with the aim of achieving voice function that is consistent with gender identity and supporting psychosocial well-being.
Keywords: transgender individuals, voice disorders, etiology, clinical picture, therapeutic approaches